IDENTIFIKASI GAYA BELAJAR (VISUAL, AUDITORI, KINESTETIK) SISWA KELAS X IPS 2 SMAN 2 TARUNA BHAYANGKARA - Fajar Wahyu Prasetyo; Ratna Wulandari; Desi Yunita Putri (BIMBINGAN DAN KONSELING BANYUWANGI, 2023)
This study aims to determine the learning styles (visual, auditory, kinesthetic) of class X IPS 2 SMA Negeri 2 Taruna Bhayangkara. This research is a type of descriptive research. The collection of data used in this study is to use the main data in the form of a learning style questionnaire. The population in this study were all 30 students of class X with different levels of academic ability. Data analysis in this study used quantitative analysis techniques. The results showed that as a whole the learning styles most commonly possessed by class X IPS 2 students of SMA Negeri 2 Taruna Bhayangkara, especially in the sub-indicator of students with the visual type with a percentage of 37.36%, students with the auditive type with a percentage of 28.06% and students with the kinesthetic type with a percentage of 32.35%. Based on the results of data processing that has been done, it can be concluded that the learning style of class X IPS 2 students of SMA Negeri 2 Taruna Bhayangkara is dominated by the visual type learning style with a percentage of 37.36%.